Odpowiedzi

2010-01-23T17:13:06+01:00
6 razy (-9)= -54
-4) razy 1/2=-2
(-10) razy 1,5=-15
(-2/3)razy (-2/5)=4/15
(-18):3=-6
2,2:(-2)=-11
0,8 razy (-5)=-0.40
(-9) razy (- 2/3)=-18/28
(-3):(- 1/3)=1/3


2010-01-23T17:14:04+01:00
6*(-9)=-54
(-4)*1/2=-2
(-10)*1,5=-15
(-2/3)*(-2/5)=4/15
(-18):3=-6
2,2:(-2)=-1,1
0,8*(-5)=-4
(-9)*(- 2/3)=6
(-3):(- 1/3)=9
Najlepsza Odpowiedź!
2010-01-23T17:30:36+01:00
6 x (-9) = -54
(-4) x 1/2 = -2
(-10) x 1,5 = -15
(-2/3) x (-2/5) = 4/15
(-18) : 3 = -6
2,2 : (-2) = -1,1
0,8 x (-5) = -4
(-9) x (- 2/3) = 6
(-3) : (- 1/3) = 9